2021
DOI: 10.1038/s41467-021-23939-7
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive period for rescuing parvalbumin interneurons connectivity and social behavior deficits caused by TSC1 loss

Abstract: The Mechanistic Target Of Rapamycin Complex 1 (mTORC1) pathway controls several aspects of neuronal development. Mutations in regulators of mTORC1, such as Tsc1 and Tsc2, lead to neurodevelopmental disorders associated with autism, intellectual disabilities and epilepsy. The correct development of inhibitory interneurons is crucial for functional circuits. In particular, the axonal arborisation and synapse density of parvalbumin (PV)-positive GABAergic interneurons change in the postnatal brain. How and whethe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 75 publications
1
40
0
Order By: Relevance
“…Moreover, an mTOR inhibitor rapamycin can correct the spine pruning defects and ASD-relevant behaviors in TSC2 ± mice, but not in TSC2 ±: ATG7 cKO mice [ 33 ]. A most recent study has reported the similar results in parvalbumin (PV) cell-restricted TSC1 conditional haploinsufficient and knockout mice, which show transient autophagy dysfunctions, a loss of perisomatic innervation and social behavior deficits [ 34 ]. Moreover, treatment with rapamycin in a sensitive period rescues PV cell connectivity and social behavior in TSC1 conditional haploinsufficient mice [ 34 ].…”
Section: Evidence For Autophagy Dysregulation In Neurodevelopmental Disordersmentioning
confidence: 87%
See 1 more Smart Citation
“…Moreover, an mTOR inhibitor rapamycin can correct the spine pruning defects and ASD-relevant behaviors in TSC2 ± mice, but not in TSC2 ±: ATG7 cKO mice [ 33 ]. A most recent study has reported the similar results in parvalbumin (PV) cell-restricted TSC1 conditional haploinsufficient and knockout mice, which show transient autophagy dysfunctions, a loss of perisomatic innervation and social behavior deficits [ 34 ]. Moreover, treatment with rapamycin in a sensitive period rescues PV cell connectivity and social behavior in TSC1 conditional haploinsufficient mice [ 34 ].…”
Section: Evidence For Autophagy Dysregulation In Neurodevelopmental Disordersmentioning
confidence: 87%
“…A most recent study has reported the similar results in parvalbumin (PV) cell-restricted TSC1 conditional haploinsufficient and knockout mice, which show transient autophagy dysfunctions, a loss of perisomatic innervation and social behavior deficits [ 34 ]. Moreover, treatment with rapamycin in a sensitive period rescues PV cell connectivity and social behavior in TSC1 conditional haploinsufficient mice [ 34 ]. Apart from TSC1/2 models of ASD, recent studies have reported the impaired expression of autophagy related protein Beclin1 in animal models of ASD including Cc2d1a ± and ADNP ± mice [ 35 , 36 ].…”
Section: Evidence For Autophagy Dysregulation In Neurodevelopmental Disordersmentioning
confidence: 87%
“…A relatively high and broad age range of the participants in the context of neurodevelopment (i.e., age range 4–17) could possibly have contributed to this difference, and research in only younger individuals might show more robust improvement of the symptoms [ 108 ]. Indeed, Amegandjin et al identified a sensitive window for mTOR inhibitor treatment during the third postnatal week to rescue social behavior in adult TSc1 mutant mice [ 109 ]. This effect is mediated by rescuing parvalbumin interneuron connectivity in these mice [ 109 ].…”
Section: From Asd Development To Windows Of Treatment Opportunitymentioning
confidence: 99%
“…Indeed, Amegandjin et al identified a sensitive window for mTOR inhibitor treatment during the third postnatal week to rescue social behavior in adult TSc1 mutant mice [ 109 ]. This effect is mediated by rescuing parvalbumin interneuron connectivity in these mice [ 109 ]. In the cortex, these cells are important in modulating sensory responses and therefore also important for the development of normal social behaviors [ 39 , 59 ].…”
Section: From Asd Development To Windows Of Treatment Opportunitymentioning
confidence: 99%
“…To investigate whether Sox6 activity during postnatal development plays a role in the process of synapse formation and maturation, we used a gene gun transfection approach in cortical organotypic cultures, using a previously characterized plasmid which specifically targets Pvalb + cells (P G67 ; Chattopadhyaya et al, 2004 , 2007 , 2013 ; Baho et al, 2019 ; Di Cristo et al, 2007 ). This technique allows (1) visualization of Pvalb + basket cells' axonal branching and synaptic innervation onto excitatory neurons during development at high resolution and (2) manipulation of gene expression in isolated Pvalb + neurons in an otherwise wild-type background, allowing for single-cell perturbation and cell-autonomous studies ( Baho et al, 2019 ; Amegandjin et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%